Aurora Villa, pionera de la enseñanza de la educación física femenina en España. // Aurora Villa, pioneer in the girls`s physic education in Spain. - José Luis Rodríguez Villa (Consejería de Educación, Cultura y Deporte del Gobierno de Cantabria (CRIEME), 2017)
(ES) Aurora Villa, nacida en Madrid en 1913, cursó estudios en el Instituto Escuela, centro educativo introductor de nuevas pedagogías; allí ejerció como profesora de educación física. La atracción por los deportes, unida a un espíritu lleno de constancia, fortaleza y vitalidad, la llevó a ser una de las primeras atletas españolas; practicó también la natación y el esquí, cosechando triunfos y ré- cords. Se hizo médico, fue especialista oftalmólogo y pionera en el tratamiento del estrabismo. Hablaba correctamente tres idiomas: francés, inglés y alemán. Ejerció hasta los 84 años. // (EN) Aurora Villa born in Madrid in 1913, and studied at the Instituto- Escuela, an experimental teaching facility pioneering innovative teaching methods where she subsequently became teacher of sports and gymnastics; her love of sport combined with a personality characterized by perseverance, strength and vitality led her to become one of the first female athletes in Spain. As a swimmer and skier she also celebrated triumphs and set new records. After qualifying as a doctor, she became a specialist in Ophtalmology and pioneared the treatment of the strabismus in Spain; she spoke three foreign languages fluently: French, English and German. Her professional career continued up to the age of eighty four.